UHPLC-ESI-MS analysis of Javanese Tamarindus indica leaves from various tropical zones and their beneficial properties in relation to antiobesity - Tri Wiyono, Andri Frediansyah, Eti Nurwening Sholikhah, Woro Rukmi Pratiwi (Journal of Applied Pharmaceutical Science, 2022)
Numerous therapeutic strategies for treating and preventing obesity have been proposed. Pharmacotherapy with orlistat, sibutramine, or antagonists of cannabinoid receptors still has some side effects. Tamarindus indica leaves are said to have lipid-lowering properties, suggesting that they could be used as antiobesity agents. The purpose of this study is to analyze the phytochemicals of the tamarind leaf extract grown in a variety of climates and to determine its antilipase and antiamylase activity. The phytochemical profile of T. indica leaf extracts from various tropical zones was investigated using ultrahigh-performance liquid chromatography in conjunction with electrospray ionization high-resolution mass spectrometric analysis (UHPLC-ESI-MS). Followed by metabolite annotation using Compound Discoverer 3.2 software. Antiobesity-related properties were measured including antioxidant capacity, antilipase and antiamylase activity, total phenolic and flavonoid content, and vitexin level of the extract. The enzyme pancreatin and p-nitrophenylbutyrate were used to assess the antilipase activity. Meanwhile, an antiamylase assay was carried out by measuring starch hydrolysis by pancreatin in the presence of extract. sThe results indicated that the antioxidant activity of the tamarind leaf extract was more proportional to the total phenol content (r = 0.998) than to the total flavonoids (r = −0.379) as determined by the 2,2-diphenyl-1-picrylhydrazyl assay. Tamarind leaves grown in tropical monsoon climates were found to be significantly capable of inhibiting lipase enzymes at 3.8 μg/ml (p = 0.0026). Along with flavonoids, it is believed that sesquiterpenes, alkaloids, and steroids contribute to the high synergistic lipase inhibition activity. According to enzyme kinetics analysis, the pattern of inhibition resembled that of mix-mode inhibition. This information is beneficial for standardizing the tamarind leaf extract for use in the development of herbal medicines. Further research is recommended, particularly to determine the extract’s activity against other enzymes or proteins implicated in obesity, such as lipoprotein lipase, leptins, and phosphatidic acid phosphatase.
Keywords: Kö ppen–Geiger climate zone, Tamarindus indica, UHPLCESI-MS, antiobesity, lipase inhibitory